Corporate Political Strategy and Legislative Decision Making: A Review and Contingency Approach - Keim, Gerald D.; Zeithaml, Carl P. (Academy of Management Review, 1986)
Gerald D. Keim, Carl P. Zeithaml, Corporate Political Strategy and Legislative Decision Making: A Review and Contingency Approach, The Academy of Management Review, Vol. 11, No. 4 (Oct., 1986), pp. 828-843